2003
DOI: 10.1021/ef0300343
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nanosized Iron in Slurry-Phase Fischer−Tropsch Synthesis

Abstract: The Fischer−Tropsch (F−T) activity of three α-Fe2O3-based materials, two unsupported nanosized, NANOCAT (3 nm) and BASF (20−80 nm), and a supported micrometer-sized (32.5 μm) UCI, were measured with respect to total hydrocarbon production from synthesis gas (H2/CO ∼ 2/1). All three oxides were initially reduced under CO at 553 K in ethylflopolyolefin-164 solvent, and the extent of their reduction was established by monitoring CO2 evolution. The ease of reduction of α-Fe2O3 followed the order:  UCI > NANOCAT > … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 34 publications
2
26
0
1
Order By: Relevance
“…2), is to be expected, but has not been shown unequivocally. It has been shown that catalysts containing very small iron crystallites are not as active for the Fischer-Tropsch synthesis as catalysts containing larger crystallites [32,101]. It is presently not clear whether this is caused by a decrease in the intrinsic activity with crystal size or whether the size dependence is introduced due to a size-dependent phase transformation (vide supra).…”
Section: Iron-based Catalystsmentioning
confidence: 99%
“…2), is to be expected, but has not been shown unequivocally. It has been shown that catalysts containing very small iron crystallites are not as active for the Fischer-Tropsch synthesis as catalysts containing larger crystallites [32,101]. It is presently not clear whether this is caused by a decrease in the intrinsic activity with crystal size or whether the size dependence is introduced due to a size-dependent phase transformation (vide supra).…”
Section: Iron-based Catalystsmentioning
confidence: 99%
“…The difference in product selectivity among these catalysts has been attributed to differences in their capabilities to catalyze CO dissociation, hydrogenation, CO insertion, and chain growth [8,[20][21][22]. Fe [23], Co [24], and Ru exhibit excellent CO dissociation and hydrogenation activities; hence serve as typical CO hydrogenation catalysts that produce linear hydrocarbons as major products and C 2+ oxygenates as minor products. Ni is an excellent methanation catalyst due to its CO dissociation and hydrogenation activity [22,[25][26][27].…”
Section: Co Hydrogenation Networkmentioning
confidence: 99%
“…In a desire to reduce costs of large-scale catalytic systems, for example, in the refinery industry, researchers in the 1950s began to produce smaller catalytic particles in order to profit from the resulting advantageous characteristics described above [26]. Thereby, the size was lowered from 100 nm in the beginning to less than 1 nm today [101]. Both, top-down and bottom-up approaches are conceivable for the synthesis of nanoparticle catalysts.…”
Section: Synthesis Of Nanoparticle Catalystsmentioning
confidence: 99%